An empirical examination of the relationship between corporate social responsibility disclosure and financial performance in an emerging market - Saleh, Mustaruddin; Zulkifli, Norhayah; Muhamad, Rusnah (2008)
This study, using longitudinal data analysis, attempts to address the question of whether CSR is linked to financial performance for PLCs in Malaysia. Despite CSR disclosure being at a nascent stage in Malaysia, the findings of this study solidly support the outcome of the majority of results in developed markets. It was found to be positively related to financial performance. This suggests that local firms can achieve advanced levels of financial performance if they engage in social activities. The findings also confirm that there is limited evidence of a significant effect of CSR on financial performance in a long-term relationship.